Regulation of Customary and Official Village Authority in Managing Village Assets in Bali - I Gede Mahada Arsadana; Ngesti Dwi Prasetyo; I Nyoman Nurjaya (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
The dualism of the village government system in Bali, consisting of Customary Villages and Service Villages, creates its own legal dynamics in the management of village assets. The enactment of Bali Provincial Regulation Number 4 of 2019 concerning Customary Villages strengthens the legal position of Customary Villages, including their authority over the Padruwen of Customary Villages as customary village assets. However, this regulation raises normative issues due to differences in the legal construction of village asset management with Law Number 6 of 2014 concerning Villages. This condition creates overlapping authority, unclear asset ownership status, and potential disputes between Customary Villages and Service Villages. This study aims to analyze the legal meaning of the Padruwen of Customary Villages according to Bali Provincial Regulation Number 4 of 2019 and formulate regulations that provide legal certainty in the management of assets between Customary Villages and Service Villages. This research is a normative legal research using a statutory approach, a conceptual approach, and a historical approach. The legal materials used consist of primary, secondary, and tertiary legal materials obtained through literature studies and analyzed qualitatively using prescriptive methods. The analysis focused on identifying disharmonious norms between national and regional regulations governing village asset management. The Padruwen Desa Adat (Customary Village) is not only interpreted as an asset of economic value but also as a representation of the collective identity, ancestral rights, and autonomy of indigenous communities in Bali. Current regulations still show disharmony regarding the legal subject of asset ownership, management authority, asset classification, oversight mechanisms, and accountability systems. This disharmony has resulted in legal uncertainty and has the potential to lead to conflicts in village asset management. Therefore, regulatory harmonization is needed through a clear division of authority, strengthening legal recognition of Customary Village assets, and establishing an integrated asset management model between state law and customary law to achieve legal certainty, justice, and sustainable protection for village assets in Bali.